Heat-conducting gasket as well as preparation method and application thereof

By introducing modified alumina and small-particle alumina powder into the thermal gasket, combined with the optimized adhesive layer design, the problem of the surface viscosity and strength of the ultra-thin thermal gasket cannot be taken into account, and efficient heat conduction and good viscosity are achieved, which is suitable for the heat dissipation and miniaturization needs of electronic equipment.

CN119823578APending Publication Date: 2025-04-15SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510052635.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The problems of the surface viscosity and strength of existing ultra-thin thermal conductivity gaskets cannot be taken into account, resulting in low heat dissipation efficiency of electronic equipment and limited equipment miniaturization and lightness.

Method used

A reasonable organic formula is used to introduce modified alumina A, B and C, and control the grading of different particle sizes, and combine small-particle-sized alumina powder as thermal filler to prepare a thermal gasket matrix; a small-particle-sized alumina is introduced into the adhesive layer to improve surface viscosity and reduce the obstruction of the thermal coating on the heat conduction path.

Benefits of technology

The preparation of ultra-thin thermal conductivity gaskets is realized, with high thermal conductivity, good viscosity and low thermal resistance, which is suitable for the heat dissipation needs of electronic equipment, and promotes the miniaturization and thinning of the equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a heat-conducting gasket and a preparation method and application thereof, and relates to the technical field of heat dissipation materials. A reasonable organic formula is adopted, modified aluminum oxide A, modified aluminum oxide B and modified aluminum oxide C are introduced, particle size grading of different modified aluminum oxide is controlled, small-particle-size aluminum oxide powder is introduced and matched to serve as heat conduction filler, and manufacturing of the high-heat-conductivity-coefficient and ultrathin heat conduction gasket is achieved; and small-particle-size modified aluminum oxide is introduced into the adhesive layer, so that the obstruction of the heat-conducting coating on a heat-conducting passage is reduced, the surface viscosity of the heat-conducting gasket is improved, and the heat-conducting capacity of the gasket is reserved to the maximum extent. In addition, the surface viscosity of the heat-conducting gasket can be controlled, the thickness of the heat-conducting adhesive can be changed according to different parameters of a surface spin coater, and the heat-conducting gaskets with different viscosities can be adjusted according to requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat dissipation materials, and in particular to a thermally conductive pad and a preparation method and application thereof. Background Art

[0002] As an important heat dissipation material in electronic devices, the main function of thermal conductive gaskets is to establish an effective heat conduction channel between the heating device and the heat dissipation device, thereby improving the heat dissipation efficiency. However, traditional thermal conductive gaskets have many limitations, such as large thickness, insufficient thermal conductivity and limited surface viscosity. These problems seriously restrict the heat dissipation efficiency, miniaturization process and process mounting convenience of electronic equipment. The ideal thermal conductive material not only needs to have excellent thermal conductivity, mechanical strength, temperature resistance, insulation performance, etc., but also should have sufficient viscosity to meet the heat dissipation needs of electronic equipment in various working environments.

[0003] In addition, as electronic devices develop towards lighter, thinner and more compact directions, higher requirements are also placed on the thickness of thermally conductive gaskets, that is, to reduce the thickness as much as possible while ensuring performance, so as to reduce space occupation and improve the integration of equipment. In this context, the development of a new type of ultra-thin viscosity controllable thermally conductive gasket is of great significance to promote the development of electronic equipment heat dissipation technology. This can not only improve the heat dissipation efficiency of electronic equipment and extend the service life of the equipment, but also provide strong material support for the miniaturization and thinness of electronic equipment.

[0004] However, there is still a shortage of ultra-thin thermal conductive gaskets of 0.1-0.2 mm on the market, and aspects such as viscosity, gasket strength and thermal conductivity cannot be taken into account.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a thermally conductive gasket and a preparation method and application thereof, aiming to solve the problem that the surface viscosity and strength of the current ultra-thin thermally conductive gasket cannot be taken into account at the same time.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a thermally conductive gasket, comprising a thermally conductive gasket substrate and an adhesive layer attached to the thermally conductive gasket substrate;

[0009] Wherein, the thermal conductive pad substrate comprises, by mass: 100 parts of vinyl-terminated polydimethylsiloxane, 0-20 parts of vinyl MQ silicone resin, 5-15 parts of side hydrogen-containing silicone oil, 80-120 parts of terminal hydrogen-containing silicone oil, 3-7 parts of catalyst, 0.5-5 parts of inhibitor, 0-2 parts of color paste, 1200-1700 parts of modified alumina A, 50-150 parts of modified alumina B and 300-900 parts of modified alumina C; modified alumina A is spherical alumina with a particle size of 3μm-7μm, modified alumina B is spherical alumina with a particle size of 8μm-15μm, and modified alumina C is single crystal alumina with a particle size of 0.1μm-2μm;

[0010] Wherein, the raw materials of the adhesive layer include 100 parts of acrylate photocurable adhesive and 0-50 parts of modified aluminum oxide C, calculated by weight.

[0011] In an optional embodiment, the thickness of the thermally conductive gasket substrate is 0.10 mm-0.12 mm, and the thickness of the adhesive layer is 0.005 mm-0.020 mm;

[0012] and / or, the viscosity of the vinyl-terminated polydimethylsiloxane is 90 mPa.s-1000 mPa.s;

[0013] And / or, the viscosity of the vinyl MQ silicone resin is 5000mPa.s-8000mPa.s, the resin content is 40%-60%, and the vinyl content is 0.7%-1.2%.

[0014] In an optional embodiment, the viscosity of the side hydrogen-containing silicone oil is 90mPa.s-130mPa.s, and the hydrogen content is 0.05%-0.3%;

[0015] And / or, the viscosity of the terminal hydrogen-containing silicone oil is 500mPa.s-1500mPa.s, and the hydrogen content is 0.005%-0.015%.

[0016] In an optional embodiment, the catalyst is a platinum catalyst, and the platinum content is 3000ppm-5000ppm.

[0017] In an alternative embodiment, the inhibitor is an alkynol inhibitor.

[0018] In an optional embodiment, the color paste is black silica gel color paste.

[0019] In a second aspect, the present invention provides a method for preparing a thermally conductive gasket according to any one of the aforementioned embodiments, comprising: preparing ingredients according to the composition of the thermally conductive gasket substrate, mixing the raw materials to obtain a thermally conductive gelatin mass, and curing and forming the thermally conductive gelatin mass to obtain the thermally conductive gasket substrate;

[0020] The ingredients are prepared according to the composition of the adhesive layer, and the acrylate light-curing adhesive and the modified aluminum oxide C are mixed to obtain a thermally conductive adhesive;

[0021] The thermal conductive adhesive is applied to the thermal conductive gasket substrate and subjected to a light curing treatment.

[0022] In an optional embodiment, the process of preparing the thermally conductive gasket substrate includes: stirring and removing bubbles from the raw materials to obtain a thermally conductive gel mass, calendering and laminating the thermally conductive gel mass with a release film, and heating at 140° C. to 160° C. for 5 min to 15 min to solidify and form a thermally conductive gasket with a thickness of 0.10 mm to 0.12 mm;

[0023] Preferably, the preparation process of the thermally conductive gelatinous group includes: stirring, grinding and vacuum stirring the raw materials in sequence.

[0024] In an optional embodiment, the thermally conductive adhesive is spin-coated on the thermally conductive gasket substrate and cured under ultraviolet light of 360nm-370nm for 1min-5min.

[0025] In a third aspect, the present invention provides use of the thermally conductive gasket according to any one of the aforementioned embodiments or the thermally conductive gasket prepared by any one of the preparation methods according to the aforementioned embodiments in preparing electronic devices.

[0026] The present invention has the following beneficial effects: the present invention adopts a reasonable organic formula, introduces modified alumina A, modified alumina B and modified alumina C, controls the particle size distribution of different modified aluminas, introduces small-particle-size alumina powder as a thermally conductive filler, and realizes the production of a high thermal conductivity coefficient and an ultra-thin thermally conductive gasket; small-particle-size modified alumina is introduced into the adhesive layer, which reduces the obstruction of the thermal conductive coating to the thermal conductive path, improves the surface viscosity of the thermally conductive gasket, and retains the thermal conductivity of the gasket to the greatest extent.

[0027] In addition, the thermally conductive gasket provided by the present invention can also achieve controllable surface viscosity. The thickness of the thermally conductive adhesive can be changed according to different parameters of the surface spin coater, and thermally conductive gaskets with different viscosities can be adjusted according to needs. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0029] In view of the current shortage of ultra-thin thermally conductive gaskets of 0.1-0.2 mm and the problems that viscosity, gasket strength and thermal conductivity cannot be taken into account at the same time, the present invention provides an ultra-thin thermally conductive gasket with controllable viscosity, which realizes the preparation of ultra-thin thermally conductive gaskets while ensuring the viscosity and strength of the gasket, and has a good application prospect.

[0030] The embodiment of the present invention provides a thermally conductive gasket, comprising a thermally conductive gasket substrate and an adhesive layer attached to the thermally conductive gasket substrate. The formulas of the thermally conductive gasket substrate and the adhesive layer are optimized, specifically as follows:

[0031] [Thermal conductive pad substrate]

[0032] The raw materials of the thermal conductive pad substrate include, by weight: 100 parts of vinyl-terminated polydimethylsiloxane, 0-20 parts of vinyl MQ silicone resin, 5-15 parts of side hydrogen-containing silicone oil, 80-120 parts of end hydrogen-containing silicone oil, 3-7 parts of catalyst, 0.5-5 parts of inhibitor, 0-2 parts of color paste, 1200-1700 parts of modified alumina A, 50-150 parts of modified alumina B and 300-900 parts of modified alumina C. Among them, the particle sizes of modified alumina B, modified alumina A and modified alumina C gradually decrease, and modified alumina C is a single crystal alumina with a smaller particle size.

[0033] It should be noted that, because the gasket is extremely thin, if the organic components are not cross-linked properly, the product cannot be formed, and the poor powder ratio will cause defects in sample production, which will lead to a decrease in thermal conductivity and thermal resistance. The thermally conductive gasket matrix provided by the embodiment of the present invention adopts a reasonable organic formula, introduces modified alumina A, modified alumina B and modified alumina C, and controls the particle size distribution of different modified aluminas, introduces small-particle alumina powder as a thermal conductive filler, and realizes the production of high thermal conductivity and ultra-thin thermal conductive gaskets.

[0034] Specifically, when the amount of terminal vinyl polydimethylsiloxane is 100 parts, the amount of vinyl MQ silicone resin can be 0 parts, 3 parts, 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, etc.; the amount of side hydrogen-containing silicone oil can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, etc.; the amount of terminal hydrogen-containing silicone oil can be 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, etc.; the amount of catalyst can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, etc.; the amount of inhibitor can be 0.5 parts, 1.0 parts, 2.0 parts, 3.0 parts, 4.0 parts, 5.0 parts, etc.; the amount of color paste can be 0.0 parts, 0.5 parts, 1.0 parts, 2.0 parts, 3.0 parts, 4.0 parts, 5.0 parts, etc. , 1.0 parts, 1.5 parts, 2.0 parts, etc.; the amount of modified alumina A can be 1200 parts, 1250 parts, 1300 parts, 1350 parts, 1400 parts, 1450 parts, 1500 parts, 1550 parts, 1600 parts, 1650 parts, 1700 parts, etc.; the amount of modified alumina B can be 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, etc.; the amount of modified alumina C can be 300 parts, 350 parts, 400 parts, 450 parts, 500 parts, 550 parts, 600 parts, 650 parts, 700 parts, 750 parts, 800 parts, 850 parts, 900 parts, etc.

[0035] Further, modified alumina A is spherical alumina with a particle size of 3 μm-7 μm, modified alumina B is spherical alumina with a particle size of 8 μm-15 μm, and modified alumina C is single crystal alumina with a particle size of 0.1 μm-2 μm. Modified alumina A, modified alumina B and modified alumina C are all purchased from Ya'an Baitu High-tech Materials Co., Ltd.

[0036] Specifically, the particle size of modified alumina A can be 3μm, 4μm, 5μm, 6μm, 7μm, etc.; the particle size of modified alumina B can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.; the particle size of modified alumina C can be 0.1μm, 0.5μm, 0.8μm, 1.0μm, 1.3μm, 1.5μm, 1.8μm, 2.0μm, etc.

[0037] In some embodiments, the viscosity of the vinyl-terminated polydimethylsiloxane is 90 mPa.s-1000 mPa.s, such as 90 mPa.s, 100 mPa.s, 200 mPa.s, 300 mPa.s, 400 mPa.s, 500 mPa.s, 600 mPa.s, 700 mPa.s, 800 mPa.s, 900 mPa.s, 1000 mPa.s, etc. The vinyl-terminated polydimethylsiloxane is a commercially available raw material, and its viscosity is the viscosity at 25° C. The viscosity within the above range can ensure the strength and other properties of the gasket after curing.

[0038] Vinyl MQ silicone resin is a kind of organic silicone resin composed of monofunctional Si-O unit (M unit) and tetrafunctional Si-O unit (SiQZ referred to as Q unit), and has a double-layer structure and compact spherical shape, which can effectively improve the tensile strength and bending resistance of thermal conductive silicone gaskets. Vinyl MQ silicone resin is a commercially available raw material, such as Shandong Dayi Chemical Co., Ltd.

[0039] In some embodiments, the viscosity of the vinyl MQ silicone resin is 5000mPa.s-8000mPa.s, such as 5000mPa.s, 6000mPa.s, 7000mPa.s, 8000mPa.s, etc.; the resin content of the vinyl MQ silicone resin can be 40%-60% (mass fraction), such as 40%, 45%, 50%, 55%, 60%, etc.; the vinyl content of the vinyl MQ silicone resin is 0.7%-1.2% (mass fraction), such as 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, etc.

[0040] The main difference between side hydrogen-containing silicone oil and end hydrogen-containing silicone oil is the different positions of hydrogen atoms in the siloxane molecule. End hydrogen-containing silicone oil refers to polydimethylsiloxane containing highly active Si-H bonds at both ends of the siloxane molecule, while side hydrogen-containing silicone oil contains hydrogen atoms on the side chains of the siloxane molecule. Both side hydrogen-containing silicone oil and end hydrogen-containing silicone oil are commercially available raw materials. The main purpose of introducing side hydrogen-containing silicone oil and end hydrogen-containing silicone oil at the same time in the embodiment of the present invention is: the side hydrogen-containing silicone oil plays a cross-linking role, and it forms a cross-linked network structure through addition reaction with the vinyl silicone oil matrix material, thereby improving the mechanical strength and resilience of the thermal pad. The end hydrogen-containing silicone oil plays a chain extension role, and it extends the molecular chain and reduces the cross-linking density through addition reaction with the vinyl silicone oil matrix material, thereby adjusting the hardness and elasticity of the thermal pad.

[0041] In some embodiments, the viscosity of the side hydrogen-containing silicone oil can be 90mPa.s-130mPa.s, such as 90mPa.s, 100mPa.s, 110mPa.s, 120mPa.s, 130mPa.s, etc.; the hydrogen content of the side hydrogen-containing silicone oil can be 0.05%-0.3%, such as 0.05%, 0.10%, 0.20%, 0.30%, etc.

[0042] In some embodiments, the viscosity of the terminal hydrogen-containing silicone oil can be 500mPa.s-1500mPa.s, such as 500mPa.s, 800mPa.s, 1000mPa.s, 1200mPa.s, 1500mPa.s, etc.; the hydrogen content of the terminal hydrogen-containing silicone oil can be 0.005%-0.015%, such as 0.005%, 0.008%, 0.010%, 0.013%, 0.015%, etc.

[0043] The catalyst mainly plays the role of catalyzing the cross-linking reaction of the raw materials. The catalyst can be a commercially available platinum catalyst with a platinum content of 3000ppm-5000ppm, such as 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, etc.

[0044] The inhibitor mainly plays the role of controlling the reaction rate. The inhibitor can be an alkynol inhibitor, specifically benzotriazole, cyclohexanol, methylbutynol, etc.

[0045] The color paste can give the gasket color, and black color paste is generally used. Specifically, it can be commercially available black silicone color paste, which can be purchased from Shenzhen Longhuixiang Chemical Co., Ltd.

[0046] [Adhesive layer]

[0047] The raw materials of the adhesive layer include 100 parts of acrylic light-curing adhesive and 0-50 parts of modified aluminum oxide C by weight. The embodiment of the present invention uses a mixture of adhesive and thermally conductive powder to construct a thermally conductive adhesive, which reduces the obstruction of the thermally conductive coating to the thermal conductive path, improves the surface viscosity of the thermally conductive gasket, and retains the thermal conductivity of the gasket to the greatest extent.

[0048] Specifically, when the amount of the acrylate light-curing adhesive is 100 parts, the amount of the modified aluminum oxide C can be 0 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, etc. The acrylate light-curing adhesive can be Henkel LOCTITE 3016uv light-curing glue.

[0049] In some embodiments, the thickness of the thermally conductive gasket substrate is adjusted to 0.10mm-0.12mm, such as 0.10mm, 0.11mm, 0.12mm, etc.; the thickness of the adhesive layer is 0.005mm-0.020mm, such as 0.005mm, 0.010mm, 0.015mm, 0.020mm, etc.

[0050] The present invention provides a method for preparing a thermally conductive pad, and the steps are as follows:

[0051] S1. Preparation of thermal conductive gasket substrate

[0052] Ingredients are prepared according to the composition of the thermally conductive gasket substrate, and the raw materials are mixed to obtain a thermally conductive gel mass, and the thermally conductive gel mass is solidified and formed to obtain an ultra-thin thermally conductive gasket substrate with a thickness that meets the requirements.

[0053] In some embodiments, the process of preparing a thermally conductive gasket substrate includes: stirring and degassing the raw materials to obtain a thermally conductive gel mass to prevent the introduction of bubbles into the product; calendering and laminating the thermally conductive gel mass with a release film, heating at 140°C-160°C for 5min-15min to cure and form an ultra-thin thermally conductive gasket substrate with a thickness of 0.10mm-0.12mm. The release film can be a commercially available material with a thickness of 50, 75, or 100μm.

[0054] Specifically, the curing temperature can be 140°C, 145°C, 150°C, 155°C, 160°C, etc.; the heating time can be 5 min, 8 min, 10 min, 12 min, 15 min, etc.

[0055] Furthermore, the preparation process of the thermal conductive gel group includes: stirring, grinding, and vacuum stirring the raw materials in sequence, obtaining particles with smaller particle sizes through stirring and grinding, and then removing bubbles after vacuum stirring to obtain a fully mixed and uniform thermal conductive gel group. Specifically, the stirring can be operated by a rotary stirrer, the grinding can be performed by ceramic three-roll grinding, and the vacuum stirring time can be 20 minutes to 40 minutes.

[0056] S2. Preparation of thermally conductive adhesive

[0057] The ingredients are prepared according to the composition of the adhesive layer, and the acrylate light-curing adhesive and the modified aluminum oxide C are evenly mixed to obtain a thermally conductive adhesive.

[0058] Specifically, the acrylate photocurable adhesive and the modified aluminum oxide C can be uniformly mixed by a vacuum rotary stirrer, but is not limited thereto.

[0059] S3. Forming an adhesive layer on the thermal conductive pad substrate

[0060] The thermally conductive adhesive is coated on the thermally conductive gasket substrate and subjected to a light curing treatment to obtain a thermally conductive gasket product having an adhesive layer.

[0061] Specifically, the method of coating the thermally conductive adhesive is not limited. Spin coating can be used to coat the thermally conductive adhesive on the pre-cured surface of the thermally conductive gasket using a surface spin coater. The rotation speed of the surface spin coater can be 100-15000r / min. The coating thickness is regulated according to the thickness of the adhesive layer in the final product to meet the viscosity requirements. The embodiment of the present invention improves the coating formation method, so that the surface coating of the thermally conductive gasket is comprehensive, eliminating the influence of the air contact of the poor thermal conductive medium, and at the same time, powder can be added to the coating to increase the thermal conductivity.

[0062] In some embodiments, after the thermal conductive adhesive is spin-coated on the thermal conductive gasket substrate, it is cured under 360nm-370nm ultraviolet UV lamp for 1min-5min to fully cure the acrylate light-curing adhesive. Specifically, the ultraviolet light wavelength can be 360nm, 365nm, 370nm, etc., all of which can achieve full curing of the acrylate light-curing adhesive.

[0063] It should be noted that, compared with the prior art, the embodiments of the present invention adopt reasonable organic formula, powder grading and surface coating process, and can prepare 0.1-0.12mm ultra-thin, high-strength and controllable thermal conductive pads. The thermal conductive pads can be used in the preparation of electronic devices, and can establish an effective heat conduction channel between the heating device and the heat dissipation device, thereby improving the heat dissipation efficiency.

[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0065] The raw materials in the following examples and comparative examples are as follows: the viscosity of the vinyl-terminated polydimethylsiloxane is 100 mPa·s, purchased from Zhejiang Runhe Organic Silicone New Materials Co., Ltd.; the viscosity of the vinyl MQ silicone resin is 6000 mPa·s, the resin content is 50%, and the vinyl content is 0.9%, purchased from Shandong Dayi Chemical Co., Ltd.; the viscosity of the side hydrogenated silicone oil is 110 mm 2 / s, hydrogen content is 0.12%, purchased from Zhejiang Runhe Organic Silicone New Materials Co., Ltd.; the viscosity of the end hydrogen-containing silicone oil is 500mm 2 / s, with a hydrogen content of 0.011%, purchased from Zhejiang Runhe Organic Silicon New Materials Co., Ltd.; the catalyst is a platinum catalyst with a platinum content of 5000ppm, purchased from Suzhou Beiteli Company; the inhibitor is an acetylene alcohol inhibitor purchased from Guangzhou Siyou New Materials Technology Co., Ltd.; the color paste is a black silica gel color paste purchased from Shenzhen Longhuixiang Chemical Co., Ltd. Modified alumina was purchased from Ya'an Baitu High-tech Materials Co., Ltd., the particle size of modified alumina A is 4-6μm spherical alumina, model BAH-5H4; modified alumina B is 8-15μm spherical alumina, model BAH-10H4; modified alumina C is 0.1-2μm single crystal alumina, model NSM-1S.

[0066] Example 1

[0067] This embodiment provides a thermally conductive pad and a method for preparing the same, comprising the following steps:

[0068] (1) Specifically weigh 100 parts of vinyl-terminated polydimethylsiloxane, 10 parts of vinyl MQ silicone resin, 12 parts of side hydrogen-containing silicone oil, 98 parts of terminal hydrogen-containing silicone oil, 5 parts of catalyst, 1 part of inhibitor, 0.5 parts of color paste, 1500 parts of modified alumina A, 150 parts of modified alumina B and 500 parts of modified alumina C.

[0069] (2) The raw materials in step (1) are stirred for 30 minutes by a rotary stirrer, ground 5 times by a ceramic three-roll grinder, and stirred in a vacuum for 30 minutes to obtain a thermally conductive gel mass with bubbles removed and fully mixed. The thermally conductive gel mass is laminated with a release film (thickness 0.05 mm, the same below), and heated at 150° C. for 8 minutes to cure and form an ultra-thin thermally conductive gasket of 0.10-0.12 mm.

[0070] (3) Specifically weighing 100 parts of acrylic light-curing adhesive and 20 parts of modified alumina C, and mixing them evenly with a vacuum rotary stirrer to obtain a thermally conductive adhesive; using a surface spin coater to apply the thermally conductive adhesive on a pre-cured ultra-thin thermally conductive gasket, and then curing it under a 365nm ultraviolet UV lamp for 5 minutes, and controlling the coating thickness to be 0.010mm.

[0071] Example 2

[0072] The only difference from Example 1 is that the content of organic components is different, specifically: 20 parts of vinyl MQ silicone resin, 7 parts of side hydrogen-containing silicone oil, 90.5 parts of terminal hydrogen-containing silicone oil, 6 parts of catalyst, 2 parts of inhibitor, and 1 part of color paste.

[0073] Note: The different contents of organic components refer to the fact that 100 parts of terminal vinyl polydimethylsiloxane remain unchanged, and the composition and amount of modified alumina remain unchanged.

[0074] Example 3

[0075] The only difference from Example 1 is that the content of organic components is different, specifically: 0 parts of vinyl MQ silicone resin, 9 parts of side hydrogen-containing silicone oil, 108.5 parts of terminal hydrogen-containing silicone oil, 6 parts of catalyst, 2 parts of inhibitor, and 1 part of color paste.

[0076] Example 4

[0077] The only difference from Example 1 is that the content of organic components is different, specifically: 8 parts of vinyl MQ silicone resin, 7 parts of side hydrogen-containing silicone oil, 100.5 parts of terminal hydrogen-containing silicone oil, 7 parts of catalyst, 2 parts of inhibitor, and 2 parts of color paste.

[0078] Example 5

[0079] The only difference from Example 1 is that the content of organic components is different, specifically: 12 parts of vinyl MQ silicone resin, 15 parts of side hydrogen-containing silicone oil, 91 parts of terminal hydrogen-containing silicone oil, 5 parts of catalyst, 1.5 parts of inhibitor, and 2 parts of color paste.

[0080] Example 6

[0081] The only difference from Example 1 is that the content of organic components is different, specifically: 18 parts of vinyl MQ silicone resin, 12 parts of side hydrogen-containing silicone oil, 80 parts of terminal hydrogen-containing silicone oil, 3 parts of catalyst, 0.5 parts of inhibitor, and 1 part of color paste.

[0082] Example 7

[0083] The only difference from Example 1 is that the content of organic components is different, specifically: 18 parts of vinyl MQ silicone resin, 12 parts of side hydrogen-containing silicone oil, 89.5 parts of terminal hydrogen-containing silicone oil, 7 parts of catalyst, 2.5 parts of inhibitor, and 1 part of color paste.

[0084] Example 8

[0085] The only difference from Example 1 is that the content of organic components is different, specifically: 2 parts of vinyl MQ silicone resin, 5 parts of side hydrogen-containing silicone oil, 120 parts of terminal hydrogen-containing silicone oil, 5 parts of catalyst, 2 parts of inhibitor, and 0.5 parts of color paste.

[0086] Example 9

[0087] The only difference from Example 1 is that the content of organic components is different, specifically: 20 parts of vinyl MQ silicone resin, 13.5 parts of side hydrogen-containing silicone oil, 85 parts of terminal hydrogen-containing silicone oil, 7 parts of catalyst, 0.5 parts of inhibitor, and 0.5 parts of color paste.

[0088] Example 10

[0089] The only difference from Example 1 is that the content of organic components is different, specifically: 0 parts of vinyl MQ silicone resin, 3 parts of side hydrogen-containing silicone oil, 120 parts of terminal hydrogen-containing silicone oil, 3 parts of catalyst, 0.5 parts of inhibitor, and 0 parts of color paste.

[0090] Embodiment 11

[0091] The only difference from Example 1 is that the content of organic components is different, specifically: 8 parts of vinyl MQ silicone resin, 15 parts of side hydrogen-containing silicone oil, 91.5 parts of terminal hydrogen-containing silicone oil, 7 parts of catalyst, 5 parts of inhibitor, and 0 parts of color paste.

[0092] Example 12

[0093] The only difference from Example 1 is that the content of organic components is different, specifically: 20 parts of vinyl MQ silicone resin, 15 parts of side hydrogen-containing silicone oil, 80 parts of end hydrogen-containing silicone oil, 7 parts of catalyst, 3 parts of inhibitor, and 2 parts of color paste.

[0094] Embodiment 13

[0095] The only difference from Example 1 is that the content of organic components is different, specifically: 8 parts of vinyl MQ silicone resin, 12 parts of side hydrogen-containing silicone oil, 100 parts of terminal hydrogen-containing silicone oil, 5 parts of catalyst, 1 part of inhibitor, and 0.5 parts of color paste.

[0096] Embodiment 14

[0097] The only difference from Example 1 is that the gradation of the modified powder is different, specifically, 1700 parts of modified alumina A, 150 parts of modified alumina B, and 300 parts of modified alumina C.

[0098] Embodiment 15

[0099] The only difference from Example 1 is that the gradation of the modified powder is different, specifically, 1200 parts of modified alumina A, 50 parts of modified alumina B, and 900 parts of modified alumina C.

[0100] Example 16

[0101] The only difference from Example 1 is that the ratio of the thermal conductive adhesive is different, specifically: 100 parts of acrylate photocurable adhesive and 0 parts of modified aluminum oxide C.

[0102] Embodiment 17

[0103] The only difference from Example 1 is that the ratio of the thermal conductive adhesive is different, specifically: 100 parts of acrylate photocuring adhesive and 50 parts of modified aluminum oxide C.

[0104] Comparative Example 1

[0105] The only difference from Example 1 is that the content of organic components is different, specifically: 30 parts of vinyl MQ silicone resin, 0 parts of side hydrogen-containing silicone oil, and 90 parts of terminal hydrogen-containing silicone oil. The amounts of terminal vinyl polydimethylsiloxane, catalyst, inhibitor, color paste, modified alumina A, modified alumina B, and modified alumina C remain unchanged.

[0106] Comparative Example 2

[0107] The only difference from Example 1 is that the content of organic components is different, specifically: 0 parts of vinyl MQ silicone resin, 0 parts of side hydrogen-containing silicone oil, and 130 parts of terminal hydrogen-containing silicone oil. The amounts of terminal vinyl polydimethylsiloxane, catalyst, inhibitor, color paste, modified alumina A, modified alumina B, and modified alumina C remain unchanged.

[0108] Comparative Example 3

[0109] The only difference from Example 1 is that the gradation of the modified powder is different, specifically, 2000 parts of modified alumina A, 150 parts of modified alumina B, and 500 parts of modified alumina C.

[0110] Comparative Example 4

[0111] The only difference from Example 1 is that the gradation of the modified powder is different, specifically, 1500 parts of modified alumina A, 200 parts of modified alumina B, and 500 parts of modified alumina C.

[0112] Comparative Example 5

[0113] The only difference from Example 1 is that the gradation of the modified powder is different, specifically, 1750 parts of modified alumina A, 0 parts of modified alumina B, and 400 parts of modified alumina C.

[0114] Comparative Example 6

[0115] The only difference from Example 1 is that the gradation of the modified powder is different, specifically, 1500 parts of modified alumina A, 650 parts of modified alumina B, and 0 parts of modified alumina C.

[0116] Comparative Example 7

[0117] The only difference from Example 1 is that the ratio of the thermal conductive adhesive is different, specifically: 100 parts of acrylate photocurable adhesive and 100 parts of modified aluminum oxide C.

[0118] Comparative Example 8

[0119] The only difference from Example 1 is that no thermal conductive adhesive layer is used.

[0120] Comparative Example 9

[0121] The only difference from Example 1 is that the coating thickness of the thermal conductive adhesive is 0.025 mm.

[0122] Comparative Example 10

[0123] The only difference from Example 1 is: the coating method is different: a 10 μm four-sided film applicator is used to apply the thermal conductive adhesive on the pre-cured ultra-thin thermal conductive gasket, and then cured under a 365nm ultraviolet UV lamp for 5 minutes.

[0124] Comparative Example 11

[0125] The only difference from Example 1 is: the coating method is different: the thermal conductive adhesive is coated on the pre-cured ultra-thin thermal conductive gasket using an 80-mesh screen printing plate, and then cured under a 365nm ultraviolet UV lamp for 5 minutes.

[0126] Test Example 1

[0127] The performance tests were conducted on the ultra-thin controllable viscosity thermally conductive gaskets prepared in Examples 1-17 and Comparative Examples 1-9. The results are shown in Table 1.

[0128] Test method: (1) Thermal conductivity test: Use Hot Disk TPS3500 thermal conductivity meter to test the thermal conductivity of the sample. (2) Thermal resistance test: Use Ruiling LW-9389 instrument to test, the test conditions are 80℃20psi. (3) Adhesion test: Cut 100*25mm sheet, stick it flat on the steel plate, and put it upside down vertically for 72 hours without falling off.

[0129] Table 1. Ultra-thin thermal pad performance test

[0130] Thermal conductivity / W / mK Thermal resistance (℃·in2 / W) viscosity Example 1 5.357 0.205 >72 Example 2 5.154 0.216 >72 Example 3 4.941 0.225 >72 Example 4 5.071 0.216 >72 Example 5 5.119 0.215 >72 Example 6 5.209 0.211 >72 Example 7 5.089 0.214 >72 Example 8 4.445 0.247 >72 Example 9 5.199 0.211 >72 Example 10 4.526 0.387 >72 Embodiment 11 4.609 0.322 >72 Example 12 4.954 0.278 >72 Embodiment 13 4.853 0.332 >72 Embodiment 14 5.420 0.203 >72 Embodiment 15 5.391 0.200 >72 Example 16 4.624 0.342 >72 Embodiment 17 5.841 0.148 >72 Comparative Example 1 Thermally conductive adhesive cannot solidify / / Comparative Example 2 Thermally conductive adhesive cannot solidify / / Comparative Example 3 The thermal conductive glue group cannot be stirred evenly / / Comparative Example 4 There are a lot of pinhole defects in the gasket / / Comparative Example 5 The thermal conductive glue group cannot be stirred evenly / / Comparative Example 6 There are a lot of pinhole defects in the gasket / / Comparative Example 7 5.910 0.124 0.5h Comparative Example 8 6.060 0.119 0h Comparative Example 9 4.997 0.375 >72 Comparative Example 10 4.806 0.371 >72 Comparative Example 11 4.951 0.317 >72

[0131] It can be seen from the above test results that the thermally conductive gasket provided by the embodiment of the present invention is ultra-thin and has good thermal conductivity, good viscosity and low thermal resistance.

[0132] It can be seen from the test results of Example 1 and Comparative Examples 1-2 that an effective cross-linking network cannot be formed in the unreasonable organic components, resulting in the gasket being unable to be cured and formed.

[0133] It can be seen from the test results of Examples 1, 14, 15 and Comparative Examples 3-6 that unreasonable powder grading will cause defects in the thermal conductive gasket.

[0134] It can be seen from the test results of Example 1 and Comparative Example 5 that there is too much powder in the thermally conductive adhesive and the viscosity of the thermally conductive gasket decreases.

[0135] It can be seen from the test results of Example 1 and Comparative Example 6 that without using a thermally conductive adhesive layer, the thermally conductive gasket has no stickiness.

[0136] It can be seen from the test results of Example 1 and Comparative Example 7 that the thickness of the thermally conductive adhesive coating is too high, and the performance of the thermally conductive gasket is significantly reduced.

[0137] From the test results of Example 1 and Comparative Examples 8-9, it can be seen that the four-sided coater significantly reduces the performance of the thermal conductive gasket, the uncoated part of the screen printing cannot contact the thermal conductive medium and retains air, and the thermal conductivity coefficient is significantly reduced.

[0138] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A thermally conductive pad, characterized in that: It includes a thermally conductive pad substrate and an adhesive layer attached to the thermally conductive pad substrate; Wherein, the thermally conductive pad substrate comprises, by mass: 100 parts of vinyl-terminated polydimethylsiloxane, 0-20 parts of vinyl MQ silicone resin, 5-15 parts of side hydrogen-containing silicone oil, 80-120 parts of terminal hydrogen-containing silicone oil, 3-7 parts of catalyst, 0.5-5 parts of inhibitor, 0-2 parts of color paste, 1200-1700 parts of modified alumina A, 50-150 parts of modified alumina B and 300-900 parts of modified alumina C; the modified alumina A is spherical alumina with a particle size of 3μm-7μm, the modified alumina B is spherical alumina with a particle size of 8μm-15μm, and the modified alumina C is single crystal alumina with a particle size of 0.1μm-2μm; Wherein, the raw materials of the adhesive layer include 100 parts of acrylate photocurable adhesive and 0-50 parts of the modified aluminum oxide C, calculated by weight.

2. The thermally conductive pad according to claim 1, characterized in that: The thickness of the thermally conductive gasket substrate is 0.10 mm to 0.12 mm, and the thickness of the adhesive layer is 0.005 mm to 0.020 mm; And / or, the viscosity of the vinyl-terminated polydimethylsiloxane is 90mPa.s-1000mPa.s; And / or, the viscosity of the vinyl MQ silicone resin is 5000mPa.s-8000mPa.s, the resin content is 40%-60%, and the vinyl content is 0.7%-1.2%.

3. The thermally conductive pad according to claim 1, characterized in that: The viscosity of the side hydrogenated silicone oil is 90mPa.s-130mPa.s, and the hydrogen content is 0.05%-0.3%; And / or, the viscosity of the hydrogen-terminated silicone oil is 500mPa.s-1500mPa.s, and the hydrogen content is 0.005%-0.015%.

4. The thermally conductive pad according to claim 1, characterized in that: The catalyst is a platinum catalyst, and the platinum content is 3000ppm-5000ppm.

5. The thermally conductive pad according to claim 1, characterized in that: The inhibitor is an alkynol inhibitor.

6. The thermally conductive pad according to claim 1, characterized in that: The color paste is black silica gel color paste.

7. A method for preparing the thermally conductive gasket according to any one of claims 1 to 6, characterized in that: include: The ingredients are prepared according to the composition of the thermally conductive gasket matrix, and the raw materials are mixed to obtain a thermally conductive gel mass, and the thermally conductive gel mass is solidified to obtain a thermally conductive gasket matrix; The ingredients are prepared according to the composition of the adhesive layer, and the acrylate light-curing adhesive and the modified aluminum oxide C are mixed to obtain a thermally conductive adhesive; The thermally conductive adhesive is coated on the thermally conductive pad substrate and subjected to a light curing treatment.

8. The preparation method according to claim 7, characterized in that: The process of preparing the thermally conductive gasket substrate includes: stirring and removing bubbles from the raw materials to obtain the thermally conductive gel group, calendering and laminating the thermally conductive gel group with a release film, and heating at 140° C. to 160° C. for 5 min to 15 min to solidify and form a thermally conductive gasket with a thickness of 0.10 mm to 0.12 mm; Preferably, the preparation process of the thermally conductive gelatinous group comprises: stirring, grinding and vacuum stirring the raw materials in sequence.

9. The preparation method according to claim 7, characterized in that: The thermally conductive adhesive is spin-coated on the thermally conductive gasket substrate and cured under ultraviolet light of 360nm-370nm for 1min-5min.

10. Use of the thermally conductive gasket according to any one of claims 1 to 6 or the thermally conductive gasket prepared by the preparation method according to any one of claims 7 to 9 in the preparation of electronic devices.